2019
DOI: 10.1111/ijfs.14092
|View full text |Cite
|
Sign up to set email alerts
|

Valorisation of sweet corn (Zea mays) cob by extraction of valuable compounds

Abstract: The main objective of this study was to investigate the proximate, mineral and phytochemical compositions of sweet corn cob (SCC), often neglected and regarded as agricultural waste. Compositional analysis showed that more than 60% of SCC was composed of insoluble dietary fibre, with cellulose being the major constituent. Results also showed that SCC can be a good source of non-essential protein and minerals (phosphorus, potassium and manganese). SCC had a total phenolic content of 6.74 g GAE kg À1 dry weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 45 publications
0
36
1
Order By: Relevance
“…Previous studies of the alkali hydrolysis of SCC showed that it contains 3.06 g kg −1 of total FA . Hence, this research aimed to investigate the effect of extraction parameters (enzyme concentration of FAE and XY, pH, and temperature) on the yield of FA from sweet corn cob.…”
Section: Introductioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Previous studies of the alkali hydrolysis of SCC showed that it contains 3.06 g kg −1 of total FA . Hence, this research aimed to investigate the effect of extraction parameters (enzyme concentration of FAE and XY, pH, and temperature) on the yield of FA from sweet corn cob.…”
Section: Introductioncontrasting
confidence: 62%
“…The quantification of FA was carried out according to the method described in Lau et al . Briefly, the analysis was performed with HP Agilent 1050 liquid chromatography equipped with a DAD detector, with a Zorbax SB‐C18 column (2.1 × 15 mm, 1.8 μm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, there has been a focus on sustainability and the utilisation of food waste materials in the International Journal of Food Science and Technology (Esteban & Ladero, ; Rhom & Aschemann‐Witzel, ). Thus, research has evaluated how food technology can utilise waste materials from sweet corn (Lau, Harbourne & Oruna‐Concha, ), fruit (Wang, Li & Liu, ; Theagarajan et al , ) and vegetables (Plazzotta, Sillani & Manzocco, ; Lafarga et al , ). However, potato waste utilisation has been neglected as a research topic.…”
mentioning
confidence: 99%